A cabotagem e seus impactos socioeconômicos no Estado do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
This research aims to present an analysis of the development of cabotage in Brazil and the role of this activity in the economic development of the state of Pará. Because it is a continental country, cabotage navigation in Brazil was favored between the XVI to XX centuries being the main means of cargo and passenger transportation between Brazilian ports on the coastal coast until public policies turned to the construction of highways and expansion of the road network. With the economic reopening to the international market in the 1990s, new investments were made through privatizations and concessions of port services, regulations in organized ports, and the entry of foreign companies into the waterway modal. However, during the Lula government (2002-2010) the Brazilian State resumed its position as an inducer of economic development by investing through the PAC, revitalization of the naval industry, and structural modernization of the national ports. Among these port fixes is the port Vila do Conde/PA which has increased its capacity to receive ships. In Pará its economy is primarily concentrated on ore mining and exports and based on the results achieved, the mining companies Alcoa and Mineração Rio Norte (MRN) take the bauxite from the Baixo Amazonas mesoregion loaded onto ships, sailing on the Amazon River as far as the metropolitan region of Belém, contributing to the region being one of the largest bauxite exporters in the world. Soy and corn are also transported from Mato Grosso by trucks to the Port of Santarém and the Miritituba Cargo Transshipment Station and taken by ship and barge to Porto Vila do Conde in Barcarena where they are exported to other countries. A qualitative approach was made based on bibliographic and documental research, with the reading of theses and scientific articles that talk about cabotage in Brazil and in the region, and it was also necessary to consult and analyze documents and data made available by federal agencies. At the end of the research we saw that with multimodality cabotage navigation has intensified in Pará in this XXI century in the search for new alternatives for the flow of cargoes aiming at lower cost and duration of transport.
Keywords: Cabotagem; Navegação; Brasil; Pará; Bauxita; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS